(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
The use of game technologies in the teaching of the Russian language in higher educational institutions has become an innovative approach to modern pedagogy. This paper explores the methods of integrating game technologies into the curriculum for university students in Uzbekistan. The study highlights the effectiveness of these technologies in enhancing linguistic competence, motivation, and engagement among students. Special attention is paid to the role of educators in designing and implementing game-based activities that meet the specific needs of pedagogical students. The results demonstrate that the incorporation of gaming elements can significantly improve language acquisition and foster a more dynamic and interactive learning environment.